THE IMPORTANCE OF LEGAL MARKETING - Besouchet Martins, Alexander (Revista Gênero e Interdisciplinaridade, 2021)
The present scientific study, carried out through the exploratory-descriptive methodology, through bibliographical and documentary research, aims to demonstrate the lack of regulation of the OAB regarding the use of social networks as a marketing tool versus the lack of knowledge of the dissemination tools of the activities lawyers. Likewise, it aims to conceptualize marketing and law, based on the OAB Statute. This approach also allows for the verification and analysis of the incidence of problems generated by the positions of the Regional OABs. As specific objectives established, it dealt with exemplifying situations and application within the context of the evolution of the legal profession in Brazil. The work was based on the light of marketing theorists and current legislation, enhancing the majority doctrine of the chosen branch to achieve the intended understanding of the subject